1999
DOI: 10.1177/089484539902500301
|View full text |Cite
|
Sign up to set email alerts
|

Career Development of Black Males: Case Studies

Abstract: Black American men are among the nation's most unemployed and underemployed groups (Leonard, 1985). The unemployment rate among Black Americans was 10.4% in 1995, as compared with 4.9% among White Americans, 9.3% among Hispanics, and 5.6% among all Americans (Table 644 in Bureau of the Census, 1997). In addition to racism (Brown & Ford, 1977), this situation may be partly explained by the educational attainment and vocational choices of Black males. Comparing Black and White men, Karweit (1977) found that Bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 16 publications
4
22
0
Order By: Relevance
“…Regarding differences in treatment, nearly 73% of African American participants, representing all leadership levels, reported feeling excluded, uncared for, or left out of communications. Those findings aligned with those of previous studies on African Americans in Predominantly White Institutions (Dahlvig, ), minorities in academic settings (Brittian, Sy, & Stokes, ), the career development of African American males (Chung, Baskin, & Case, ), and cross‐race mentoring (Stanley & Lincoln, ).…”
Section: The Meaning Behind Mentoringsupporting
confidence: 89%
“…Regarding differences in treatment, nearly 73% of African American participants, representing all leadership levels, reported feeling excluded, uncared for, or left out of communications. Those findings aligned with those of previous studies on African Americans in Predominantly White Institutions (Dahlvig, ), minorities in academic settings (Brittian, Sy, & Stokes, ), the career development of African American males (Chung, Baskin, & Case, ), and cross‐race mentoring (Stanley & Lincoln, ).…”
Section: The Meaning Behind Mentoringsupporting
confidence: 89%
“…Understanding more about the unique issues and concerns of racial/ethnic minorities is important (Bowman, 1993;Chung, Baskin, & Case, 1999). Because they may face stereotyping, discrimination, and environmental barriers, individuals who are racial/ethnic minorities may experience unique career development challenges (Herr & Cramer, 1997).…”
mentioning
confidence: 99%
“…Because they may face stereotyping, discrimination, and environmental barriers, individuals who are racial/ethnic minorities may experience unique career development challenges (Herr & Cramer, 1997). For example, a scarcity of same-race role models may be a barrier to some racial minority individuals' career development (Bright, Duefield, & Stone, 1998;Chung et a!., 1999;Haas & Sullivan, 1991;Hamann & Walker, 1993) because there are disproportionately fewer racial minority professionals in many career fields and academic settings (Fouad, 1995). The assumptions behind this theoretical postulate are that role models ofone's own race serve functions that models of a different racial/ethnic background do not serve and that people consider race when selecting career role models.…”
mentioning
confidence: 99%
“…This finding might reflect the different perceptions the participants had oftheir mothers and fathers; although fathers were viewed as more encouraging ofindependence than mothers, support by the mother may be particularly salient in decision making. Regarding the role of fathers, Chung, Baskin, and Case (1999) showed that the financial support and role modeling effects of a father or father figure strongly influenced the career development ofsome of their African American young men.…”
mentioning
confidence: 99%